Clinical Value of ctDNA in Hematological Malignancies (Lymphomas, Multiple Myeloma, Myelodysplastic Syndrome, and Leukemia): A Meta-Analysis - Tan, Xiangyu; Yan, Han; Chen, Lei; Zhang, Yuyang; Sun, Chunyan (Frontiers in Oncology, 2021)
Background Circulating tumor DNA (ctDNA) has offered a minimally invasive approach for detection and measurement of cancer. However, its diagnostic and prognostic value in hematological malignancies remain unclear. Materials and Methods Pubmed, Embase and Cochrane Library were searched for relating literature. Diagnostic accuracy variables and disease progression prediction data were pooled by the Meta-Disc version 1.4 software. Review Manager version 5.4 software was applied for prognostic data analysis. Results A total of 11 studies met our inclusion criteria. In terms of diagnosis, the pooled sensitivity and specificity were 0.51 (95% confidence intervals (CI) 0.38–0.64) and 0.96 (95% CI 0.88–1.00) respectively. The AUSROC (area under the SROC) curve was 0.89 (95%CI 0.75-1.03). When it comes to the prediction of disease progression, the overall sensitivity and specificity was 0.83 (95% CI 0.67-0.94) and 0.98 (95% CI 0.93-1.00) respectively. Moreover, a significant association also existed between the presence of ctDNA and the worse progression-free survival (HR 2.63, 95% CI 1.27-5.43, p=0.009) as well as overall survival (HR 2.92, 95% CI 1.53–5.57, p=0.001). Conclusions The use of ctDNA in clinical practice is promising, which may not only contribute to diagnosis, but also could predict the prognosis of patients so as to guide treatment. In the future, more studies are needed to realize the standardization of sequencing techniques and improve the detection sensitivity of explore methods.